PENGARUH CITRA MEREK, DESAIN DAN FITUR TERHADAP KEPUTUSAN PENGGUNAAN SEPEDA MOTOR BAJAJ PULSAR 135 LS PADA KOMUNITAS PULSARIAN SURABAYA - AKBAR ARYA PUTRA, RACHMADI (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Competition is getting tougher automotive world, especially the motorcycle competition. Bajaj one of the largest automotive companies in India, one of the products launched in Indonesia, namely Bajaj Pulsar 135 LS. There are many factors that cause consumers to choose Bajaj Pulsar 135 LS as a choice, among others, such as brand image, product design and product features. Based on the results of data processing in this study can be concluded that, the condition of the brand image, design and features of the Bajaj Pulsar 135 making use of LS in Surabaya Pulsarian community is quite high. While simultaneously the three variables has a significant influence on the decision the use of Bajaj Pulsar 135 LS. Partial image of the brand and design variables influence the decision of the use of Bajaj Pulsar 135 LS, while the variable feature does not affect the decision of the use of Bajaj Pulsar 135 LS. Keywords: Brand Image, Design, Features, Use decisions.